2021
DOI: 10.1016/j.cell.2021.02.050
|View full text |Cite
|
Sign up to set email alerts
|

An early cell shape transition drives evolutionary expansion of the human forebrain

Abstract: Summary The human brain has undergone rapid expansion since humans diverged from other great apes, but the mechanism of this human-specific enlargement is still unknown. Here, we use cerebral organoids derived from human, gorilla, and chimpanzee cells to study developmental mechanisms driving evolutionary brain expansion. We find that neuroepithelial differentiation is a protracted process in apes, involving a previously unrecognized transition state characterized by a change in cell shape. Furtherm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
118
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(157 citation statements)
references
References 100 publications
10
118
0
1
Order By: Relevance
“…Despite the similarities, human apical progenitors (APs; the founders stem and progenitor cells of the brain) were reported to have a longer prometaphase-metaphase length and a higher proliferative capacity (Mora-Bermudez et al, 2016), suggesting a possible contribution to the increase in the human neocortex size. In line with these findings, a recent report suggests a higher proliferative capacity of human forebrain organoid APs compared to those of gorilla organoids (Benito-Kwiecinski et al, 2021). The human organoids were found to be bigger in size and showed expanded lumens in comparison to the gorilla organoids.…”
Section: Brain Evolution In a Dish Cerebral Organoids As A Model Systsupporting
confidence: 71%
See 2 more Smart Citations
“…Despite the similarities, human apical progenitors (APs; the founders stem and progenitor cells of the brain) were reported to have a longer prometaphase-metaphase length and a higher proliferative capacity (Mora-Bermudez et al, 2016), suggesting a possible contribution to the increase in the human neocortex size. In line with these findings, a recent report suggests a higher proliferative capacity of human forebrain organoid APs compared to those of gorilla organoids (Benito-Kwiecinski et al, 2021). The human organoids were found to be bigger in size and showed expanded lumens in comparison to the gorilla organoids.…”
Section: Brain Evolution In a Dish Cerebral Organoids As A Model Systsupporting
confidence: 71%
“…By analyzing cerebral organoids of human, chimpanzee and macaque using scRNAseq and accessible chromatin profiling Kanton et al found a slower neuronal development in human organoids relative to primates. In addition, human and chimpanzee cells followed distinct cell states along progenitorto-neuron lineages, identified by a progression through stem cell states, progenitor cells of multiple brain regions including the forebrain, midbrain, hindbrain, and retina into differentiation Kanton et al, 2019;Pollen et al, 2019;Benito-Kwiecinski et al, 2021), neural progenitors (NPCs) (Otani et al, 2016), neurons via NPCs (Marchetto et al, 2019), and directly induced neurons (Schörnig et al, 2021). (Bottom) Observed neuronal phenotypes in the respective neuronal system and their uniqueness in either humans or non-human apes.…”
Section: Brain Evolution In a Dish Cerebral Organoids As A Model Systmentioning
confidence: 99%
See 1 more Smart Citation
“…Such subtle changes in neurogenesis length may not be easily recapitulated in vitro . Interestingly, timing differences at earlier stages of cortical development modeled in vitro between human and other great apes have been noted in a recent study ( Benito-Kwiecinski et al, 2021 ). In this system, neuroepithelial cells in human cerebral organoids delayed the switch to a more mature transition morphotype prior to the onset of neurogenesis compared with chimpanzee and gorilla.…”
Section: Role Of Neurogenic Period Length In Neocortex Expansion—expementioning
confidence: 68%
“…Human PSC-derived brain organoids recapitulate both temporal and spatial components of the neocortical development. Cerebral organoids at days 10–15 after seeding show tight junctions at the apical side of the SOX2-positive neural rosettes reminiscent of NECs in the developing human brain ( Benito-Kwiecinski et al, 2021 ). At week 5 of differentiation, cortical organoids possess mitotic NECs that are later replaced by vRGs ( Subramanian et al, 2017 ).…”
Section: Major Populations Of Cortical Neural Stem Cells Can Be Foundmentioning
confidence: 99%